Effects of two different educational movie concepts regarding failure management on the acquisition of new manual abilities for dental students: A pilot study - Gregory Jurs; Susanne Gerhardt-Szep; Stefan Ruttermann; Stefan Kopp; Alexander Uhse (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
The main goal of this pilot study is to evaluate if two different educational movie concepts regarding the failure management provide a statistically significant difference in the acquisition of manual abilities (in this case bending of a triangular clasp) for dental students.  The participants of this study were dental students (n=57) from the 7th semester of the Goethe University Frankfurt/Main. Before the beginning of the study, the individual manual ability of the study participants has been assessed in the form of a pretest (Pret), based on the HAM-Man (with a scale from 0= very poor to 6= very good).  Based on these results, participants of this study were stratified, randomized and divided into two different groups. The two groups watched an educational movie with (study group 1) or without (study group 2) failure management. The individual acquisition of new manual abilities (regarding the bending of a triangular clasp) after the intervention was evaluated after three different criteria (length of each side, flatness and form of the triangle) and was measured in an overall grade (from 1 = very good to 6 = very bad). The differences, tested between the groups using a Wilcoxon-Mann-Whitney test, and p-values below 0.05 were considered significant. Between study group 1(Pret=4.19, Post=2.67) and study group 2(Pret=4.18, Post=2.50) no statistically significant difference in the overall grading of each triangular clasp (p=0.68) was found.  This finding leads to the conclusion that educational movies based on failure management have no statistically significant influence on the acquisition of new manual abilities.